Tiara Handicraft dan Kaum Difabel: Strategi Pemberdayaan Ekonomi Komunitas Berkebutuhan Khusus Melalui Industri Kreatif di Sidosermo Indah Surabaya - Farid, Rifaat; Anif Muchlashin (CV Omah Kreator, 2024)
This study provides an overview of economic empowerment for people with disabilities in the creative industry of Tiara Handycraft Surabaya. The focus of empowerment is intended as a means of releasing the disabled from poverty. This research uses descriptive qualitative method. The results of this study indicate (1) The diffables are interested in joining this Tiara Handicraft due to several internal and external factors, especially from outside, namely poverty (2) The strategy used by the Handycraft Tiara is a work system that prioritizes family and working hours that are not so heavy for people with disabilities.